(3GdLGeY ddBOGAs - (3ehSi Hf GdMSjf Hf ESeGYjd GdMSjfj, CHh ESeGYjds ((3YHOGdYRjR Hf aJhM Hf UGdM GdMQGHj s)
(3ChdgG (B:s
(3CNHQfG Gdabjg GdEeGe YGde LeGd GdOjf HbQGFj Ydjg aj jhe s
(3BNQgG (B:s
(3abd dj SCdJ CHj Hf cYH ceG SCdJfj abGd dj SCdJ QShd Gddg Udi Gddg Ydjg hSde ceG SCdJfj abGd SCdJ LHQjd abGd dj gcPG hLOJg aj GddhM YfGdbde Yf QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3aj ENJdGa GdCFeI GdZQQ GdbQGA GdNeSI YTQ HQhGjGJgG GdefJNHI hWQbgG GdoebVHIs
(3YdjgG ELGRGJ s
(3hjdjg QhVI GdMaGX HJgPjH GdCdaGX s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdbQGAGJ hGdJLhjOs